2018
DOI: 10.4314/jasem.v22i10.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cr, Cd, Ni and Pb levels in commonly used cosmetics and some adverse reactions in Ibadan Metropolis, South-West Nigeria

Abstract: Skin absorption remains a major source of heavy metal toxicity in humans. This study determine the heavy metals content of selected cosmetics frequently used in Ibadan South-west Nigeria using AAS model ICE 3000 and some adverse reactions. Questionnaires administered to people of different age groups and classes in the society informed the choice of representative cosmetics for heavy metals analysis. The questionnaire revealed gender distribution usage of 84.7% and 15.3%; for female and male respectively. Cosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Based on the table, it can be inferred that most of the cosmetic users were single. Previous research revealed that unmarried females (58.9%) used more often that married (40.6%) [14] . This is the reason why after marriage most married women have less attention to their appearance that result to decrease cosmetics usage.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the table, it can be inferred that most of the cosmetic users were single. Previous research revealed that unmarried females (58.9%) used more often that married (40.6%) [14] . This is the reason why after marriage most married women have less attention to their appearance that result to decrease cosmetics usage.…”
Section: Resultsmentioning
confidence: 94%
“…Pb levels in eyeliner (87.8 ppm) and in hair -dye (21.6 ppm) was (allowed level 10 ppm). Cd levels in eyeliner (0.8 ppm), lip -gloss (0.5 ppm) and face -powder (1.8 ppm) (allowed level 0.3 ppm) (15) .…”
Section: Wwwminarjournalcommentioning
confidence: 99%
“…The levels of Cr, lead, and cadmium in cosmetics products was higher than the limits levels as follows: 1.0, 10.0, and 0.3 ppm, respectively, according to the EPA and the World Health Organization. Long time use of cosmetics is a potential source of heavy metal toxicity [44].…”
Section: Health Hazards Of Heavy Metals In Bleaching Creamsmentioning
confidence: 99%